2020
DOI: 10.1002/chem.201904862
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Anionic Cross‐Coupling Reaction of Lithium Sulfonimidoyl Alkylidene Carbenoids With Organolithiums

Abstract: The mechanistic platform for a novel nickel0‐catalyzed anionic cross‐coupling reaction (ACCR) of lithium sulfonimidoyl alkylidene carbenoids (metalloalkenyl sulfoximines) with organometallic reagents is reported herein, affording substituted alkenylmetals and lithium sulfinamides. The Ni0‐catalyzed ACCR of three different types of metalloalkenyl sulfoximines, including acyclic, axially chiral and exocyclic derivatives, with sp2 organolithiums and sp2 and sp3 Grignard reagents has been studied. The ACCR of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 135 publications
0
20
0
Order By: Relevance
“…X-Ray crystal structure analysis of the α-lithiovinyl (N-methyl)sulfoximine rac-85 revealed the eight-membered dimer 90 (Figure 8) with CÀ Li bonds and four-membered CÀ LiÀ NÀ S chelate rings of the type found in solution and by ab initio calculations. [80] DFT calculations of the exocyclic α-lithiovinyl (Nmethyl)sulfoximine 89 a also gave a structure with a fourmembered CÀ LiÀ NÀ S chelate ring.. [81] The configurational stability of α-lithiovinyl sulfoximines was studied, because of the synthetic application. [79] A 1 H NMR spectroscopic investigation of the α-lithiovinyl (Nsulfonyl)sulfoximine rac-84 in THF revealed that the phenyl groups in trans and cis position of the C=C double bond undergo a rapid topomerization at low temperatures.…”
Section: Synthesis Structure and Configurational Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…X-Ray crystal structure analysis of the α-lithiovinyl (N-methyl)sulfoximine rac-85 revealed the eight-membered dimer 90 (Figure 8) with CÀ Li bonds and four-membered CÀ LiÀ NÀ S chelate rings of the type found in solution and by ab initio calculations. [80] DFT calculations of the exocyclic α-lithiovinyl (Nmethyl)sulfoximine 89 a also gave a structure with a fourmembered CÀ LiÀ NÀ S chelate ring.. [81] The configurational stability of α-lithiovinyl sulfoximines was studied, because of the synthetic application. [79] A 1 H NMR spectroscopic investigation of the α-lithiovinyl (Nsulfonyl)sulfoximine rac-84 in THF revealed that the phenyl groups in trans and cis position of the C=C double bond undergo a rapid topomerization at low temperatures.…”
Section: Synthesis Structure and Configurational Stabilitymentioning
confidence: 99%
“…The rapid process of CÀ Li bond breaking and new formation on which the scheme is based is supported by variable temperature 13 C NMR spectroscopy of the 6 Li labelled α-lithiovinyl (N-sulfonyl)sulfoximine rac-82, which showed a collapse of the triplet signal for the α-carbon atom at low temperatures to a singlet at higher temperatures. [79] The configurational stability of the acyclic α-lithiovinyl sulfoximines ent-(Z)-92 a,b (Scheme 31), the exocyclic α-lithiovinyl sulfoximines (E,R)-95 and (Z,R)-95 (Scheme 32), and the axially chiral α-lithiovinyl sulfoximines (aS,S)-89 a and (aR,S)-89 a-c (Scheme 33) was investigated by variable temperature trapping experiments with CF 3 CO 2 D. [81] The treatment of the acyclic vinyl sulfoximines ent-(Z)-91 a,b with MeLi in ether at À 75 °C gave the corresponding acyclic α-lithiovinyl sulfoximines ent-(Z)-92 a,b, which were configurationally stable at À 70 °C in ether but completely isomerized to the corresponding (E)configured isomers ent-(E)-92 a,b, at À 35 °C. The temperature dependent 13 C NMR spectra of 6 Li labelled α-lithiovinyl (Nmethyl)sulfoximine rac-83 showed a collapse of the triplet signal of the α-carbon atom to a singlet at higher temperatures, indicating a rapid CÀ Li bond breaking and forming process.…”
Section: Synthesis Structure and Configurational Stabilitymentioning
confidence: 99%
“…In 2020, Gais and co-workers combined experimental and computational results to record a novel catalytic cycle involving the conversion of Ni-ate induced by organolithium with Nivinylidene intermediates via α-elimination. 35 The detailed Please do not adjust margins Please do not adjust margins the conventional coupling reactions due to the inertness of the sp 2 carbon-oxygen bond, which is thermodynamically and kinetically unfavorable for the oxidative addition of aryl ethers to nickel. Wang, Uchiyama, and co-workers 36 provided the theoretical support for the alternative anionic pathway through DFT calculations to identify the formation of the anionic Ni 0 -ate as the key in the process of C-O bond cleavage.…”
Section: Nickel-catalysed Processes With Organo-alkali Metal Reagentsmentioning
confidence: 99%
“…To further demonstrate the application of this method, 1bromo-4-chlorobenzene (35) and 2-thienyllithium (36) were coupled with 3 mol% Pd-PEPPSI-IPr as a catalyst to generate the desired coupling product with high selectivity in 97% yield, which was used for the synthesis of melanin-concentrating hormone receptor ligands 71 (Scheme 32b). In addition, the combination of 3-methyl-1-bromobenzene (37) and 2-thienyllithium (36) provided the coupling product 38, which was applied to prepare polymers for optoelectronic devices.…”
Section: Application Of Organo-alkali Metal Reagents In the Synthesis...mentioning
confidence: 99%
See 1 more Smart Citation